Physical Embodiment Can Produce Robot Operator’s Pseudo Presence - Tanaka, Kazuaki; Nakanishi, Hideyuki; Ishiguro, Hiroshi (Frontiers in ICT, 2015)
Recent studies have focused on humanoid robots for improving distant communication. When a user talks with a remote conversation partner through a humanoid robot, the user can see the remote partner’s body motions with physical embodiment but not the partner’s current appearance. The physical embodiment existing in the same room with the user is the main feature of humanoid robots, but the effects on social telepresence, i.e. the sense of resembling face-to-face interaction, had not yet been well demonstrated. To find the effects, we conducted an experiment in which subjects talked with a partner through robots and various existing communication media (e.g. voice, avatar and video chats). As a result, we found that the physical embodiment enhances social telepresence. However, in terms of the degree of social telepresence, the humanoid robot remained at the same level as the partner’s live-video, since presenting partner’s appearance also enhances social telepresence. To utilize the anonymity of a humanoid robot, we proposed the way that produces pseudo presence that is the sense of interacting with a remote partner when they are actually interacting with an autonomous robot. Through the second experiment, we discovered that the subjects tended to evaluate the degree of pseudo presence of a remote partner based on their prior experience of watching the partner’s body motions reproduced by a robot. When a subject interacted with an autonomous robot after interacting with a teleoperated robot (i.e., a remote operator) that is identical with the autonomous robot, the subjects tended to feel as if they were talking with a remote operator.